Come and see discipleship in the Gospel of John - Brown, Sherri (Biblical studies from the Catholic Biblical Association, 2022)
"An exploration of the invitations and imperatives embedded across the Gospel of John as the Fourth Evangelist draws audiences into his story of the good news"--